Cutaneous leishmaniasis in British troops following jungle training in Belize: Cumulative incidence and potential risk practices - Ngwa Niba Rawlings; Mark Bailey; Peter Craig; Orin Courtenay (Parasite Epidemiology and Control)
Background: British soldiers undergoing jungle training in Belize typically experience a relatively low risk of developing cutaneous leishmaniasis. However, an uncharacteristically large outbreak of cutaneous leishmaniasis occurred in 2022. This study aimed to determine the cumulative incidence of the disease and highlight potential shortcomings in personal protective measures to mitigate exposure to sand fly vector bites. Methods: A retrospective analysis was conducted on medical records of cutaneous leishmaniasis cases between 2005 and 2022, as well as on questionnaire responses regarding personal protective measures administered to cutaneous leishmaniasis cases in 2022. Data were sourced from Defence Public Health Unit, Military Environmental Health Department and British Army Training Support Unit Belize. Results: Eighty-one confirmed clinical cutaneous leishmaniasis cases were recorded between 2005 and 2022, with a substantial peak (38 cases) in 2022. Most cases occurred during the wet season. Pre-2022, the median cumulative incidence per 8-week deployment was 0.90 % (Q1–Q3: 0.34 %–1.34 %), with an annual variation of 0.2 % to 2.0 %. In 2022, the cumulative incidence spiked to 4.22 %, associated with a risk ratio of 5.3 (95 % C.I.s, 3.41, 8.16), and rising to a cumulative incidence of 7.3 % in a single unit of 450 men (33 cases) in late 2022. These values are significantly higher than the median cumulative incidence of all previous years, and to published reports for other cutaneous leishmaniasis -endemic regions. Troop responses identified limitations in the supply of optimal equipment, and in sand fly bite and leishmaniasis risk avoidance information provided by the pre-deployment health education programme. Compliance with health education advise was also suboptimal, with irregular use of insect repellents, protective clothing / head netting, and insecticide-treated hammocks. Conclusions: The reasons behind the unusually high numbers of cutaneous leishmaniasis cases and cumulative incidence in 2022 remain unclear, emphasising the need to improve personal protective measures provision and implement a comprehensive health education programme for troops undergoing jungle training in Belize.